Autoportraits photographiques américains : De la blancheur à l’ombre chez Alfred Stieglitz ; de la nudité au pastiche chez Lee Miller - Marie Cordié-Levy (Sillages Critiques)
Our aim is to analyse the reasons behind overexposure in two self-portraits, one of Alfred Stieglitz (1911), and another of Lee Miller (1930). For Stieglitz, overexposure implies a strategy to free photography from the influence of painters present in the pictorialist movement in order to create a self-determined medium. This self-portrait which acts as a signature gave full power and independence to American photography for the next hundred years. Shadows in Lake (1916) corresponds to Stieglitz’s return to anonymity and privacy. In a radically different use of overexposure, Neck manifests Lee Miller’s break with her mentor and her wish to control the images of her overexposed nudity. Using props and costumes as subterfuges to conceal her broken ego, she no longer reveals her intimacy, and in her last self-portrait (Self-portrait with Headband, 1932) will resort to pastiche to create an aura of femininity around herself.